Apomixis occurs frequently along the entire American Cordillera - Ptáček, Jan (2024)
Apomictic plants mostly occur at higher latitudes and higher elevations, where they tend to occupy deglaciated areas. By analysing samples of the alpine floras of different latitudinal zones of the Americas (Argentina, Bolivia, Ecuador, USA), we investigated whether the proportion of gametophytic apomixis is comparable between the temperate alpine zones of the Northern Hemisphere and the Southern Hemisphere and whether the proportion of apomictic species increases from the alpine tropics towards the temperate alpine zone.The reproductive systems of 196 species and 275 individuals were determined by a flow-cytometric seed screening of 999 seeds. Phylogenetic logistic regression was used to evaluate differences in the proportion of apomictic species in samples of regional alpine floras.The apomictic embryo:endosperm ratio was determined for 33 species (two pseudogamous species and 31 species with autonomous apomixis) belonging to 28 genera of 13 families. The probability of a species being apomictic did not significantly differ between the regions. The highest probability of a species being apomictic was estimated for the northern temperate zone (29.6%), followed by the tropical zone (12.5%), and the southern temperate zone (11.9%).Our results show that asexual plant reproduction by apomixis is not restricted to the alpine zone of the Northern Hemisphere and its representation in alpine floras of the Southern Hemisphere, including the alpine tropics, has been substantially underestimated.